Gender analysis of career self efficacy in university students - Arumi, Mira Sekar; Fadillah, Zalfa Eka Nurul; Fitriani, Yulia; Hermawan, Liza Gardyanie (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
Career self-efficacy plays a crucial role in shaping career-related behaviors, such as academic performance, major selection, and career transitions. However, research on career self-efficacy as a distinct variable in Indonesia remains limited. This study examines gender differences in career self-efficacy among final-semester students at a university in Jakarta. Using a comparative quantitative approach, data were collected from 370 university students through a quota sampling technique. The findings indicate a significant difference between male and female students, with men exhibiting higher career self-efficacy scores. Additionally, most respondents demonstrated high career self-efficacy, suggesting confidence in completing career-related tasks and transitioning into the workforce. However, female students, despite overall high self-efficacy, reported lower confidence in technical and leadership-oriented tasks. These findings highlight the importance of gender-responsive career counseling and skill development programs to address self-efficacy disparities. This study contributes to the understanding of career self-efficacy in Indonesia and underscores the need for more comprehensive career interventions.